Regulation of Halal Labeling on Indonesian MSME Food Products Based on Positive Law - Masriani, Yulies Tiena; Maruf, Maruf; Noor, Afif (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
Halal food has become an increasingly important concept over the past decade, driven by growing consumer awareness of the significance of halal products that comply with national positive law. However, challenges such as the high cost of halal certification and limited understanding of halal labeling remain major obstacles, particularly for micro, small, and medium-sized enterprises (MSMEs). This study aims to examine the regulation of halal labeling and its implications for consumer protection and the development of MSMEs in Indonesia. The research method employed is normative juridical, utilizing legal sources including laws and regulations. The findings indicate that Indonesia, as the country with the largest Muslim population in the world, represents a significant market for halal products. Halal labeling, as regulated by Law Number 33 of 2014 concerning Halal Product Assurance, plays a crucial role in ensuring the halal status of products for Muslim consumers. The study concludes that halal certification not only provides essential consumer protection but also opens broader access to global markets. Therefore, the government, through certification bodies such as BPJPH and MUI, plays a pivotal role in ensuring product halalness and promoting the growth of the halal industry in Indonesia.